Electrode active material, electrode, and lithium ion secondary battery
A lithium ion secondary battery electrode active material with optimized oxygen and sulfur content improves charge/discharge capacity and retention rates through enhanced dispersibility and stability, addressing the limitations of existing materials.
Patent Information
- Application Number
- JP2023198562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-11-22
AI Technical Summary
Existing electrode active materials for lithium ion secondary batteries have low oxygen content, leading to suboptimal charge/discharge capacity and capacity retention rates.
Development of an electrode active material with specific oxygen and sulfur content ratios, formulated as particles containing an organic sulfur compound, which enhances dispersibility and stability during electrochemical reactions, thereby improving charge/discharge capacity and capacity retention.
The novel electrode active material achieves higher charge/discharge capacity and better cycle characteristics by ensuring stable sulfur bonding and uniform electrode composition, maintaining performance over multiple cycles.
Smart Images

Figure 0007616329000003 
Figure 0007616329000001 
Figure 0007616329000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel electrode active material, an electrode comprising the electrode active material, and a lithium ion secondary battery comprising the electrode. [Background technology]
[0002] Lithium-ion secondary batteries have a large charge / discharge capacity and are primarily used as batteries for portable electronic devices. They are also increasingly being used as batteries for electric vehicles, and there are high hopes for improved performance.
[0003] Patent Document 1 describes a positive electrode active material obtained by heat treating high-cis-butadiene rubber together with sulfur and a vulcanization accelerator, and Patent Document 2 describes an electrode active material obtained by baking polymethyl methacrylate together with sulfur. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2015 / 050086 [Patent Document 2] JP 2021-172814 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the active materials of Patent Documents 1 and 2 only have a low oxygen content, and there is room for improvement in the charge / discharge capacity and capacity retention rate.
[0006] The present invention provides a novel electrode active material capable of improving charge / discharge capacity and capacity retention rate, an electrode comprising the electrode active material, i.e., a positive electrode or a negative electrode, and a lithium ion secondary battery comprising the electrode. [Means for solving the problem]
[0007] The present invention relates to the following electrode active material. An electrode active material comprising particles containing an organic sulfur compound, The oxygen content (mass%) in the electrode active material is A O and the sulfur content (mass%) is A S In the case where A O and A S and an electrode active material that satisfies the following formula. (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550 Effect of the Invention
[0008] According to the present invention, it is possible to provide a novel electrode active material capable of improving charge / discharge capacity and capacity retention rate, an electrode comprising the electrode active material, i.e., a positive electrode or a negative electrode, and a lithium ion secondary battery comprising the electrode.
[0009] Although it is not intended to be bound by theory, the following is believed to be the reason why the charge / discharge capacity and capacity retention rate can be improved in the present invention. That is, sulfur functions as an active material capable of repeated charge / discharge by undergoing a reversible electrochemical reaction with lithium. In the present invention, as in the conventional technology, sulfur is mixed with a polymer and fixed to the polymer through heat treatment, which is thought to suppress elution and contribute to the reversible reaction. For this reason, it is believed that the more sulfur atoms there are, the greater the charge / discharge capacity. On the other hand, in the present invention, oxygen atoms are bonded to carbon or sulfur to form C-O bonds, etc. For this reason, (1) the active material contains these polar bonds, which improves the dispersibility of the active material in an electrode slurry using water as a solvent, and a uniform electrode is produced, so that it is believed that the cycle capacity is easily maintained even after expansion and contraction associated with charge / discharge cycles. In addition, (2) the high oxygen content and the presence of this in the framework of the active material allows SS bonds to be more stably held within the structure of the active material, and therefore it is believed that the ability to maintain sulfur within the structure of the active material is high in the reaction between sulfur and lithium accompanying the insertion and desorption of lithium ions due to charge / discharge. For this reason, it is believed that the cycle capacity is likely to be maintained even after undergoing electrochemical reactions accompanying charge-discharge cycles.
[0010] In this specification, the term "cycle characteristic" refers to the characteristic of maintaining the charge / discharge capacity of a secondary battery despite repeated charging and discharging. Therefore, a secondary battery that experiences a large decrease in charge / discharge capacity and a low capacity retention rate with repeated charging and discharging has poor cycle characteristics, whereas a secondary battery that experiences a small decrease in charge / discharge capacity and a high capacity retention rate has excellent cycle characteristics. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a reaction apparatus used in the production of an electrode active material in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described. The upper and lower limit values of "more than or equal to," "less than or equal to," "more than," "less than," and the like in the description of a numerical range can be arbitrarily combined, and the numerical values in the examples can be these upper and / or lower limits. In addition, a numerical range shown as including a lower limit or an upper limit is understood to simultaneously disclose a numerical range not including the upper limit or lower limit, as long as it is not contrary to the spirit of the present invention, and conversely, a numerical range shown as not including a lower limit or an upper limit is understood to simultaneously disclose a numerical range including the lower limit or upper limit, as long as it is not contrary to the spirit of the present invention.
[0013] One embodiment of the present invention is an electrode active material comprising particles containing an organic sulfur compound, wherein the oxygen content (mass%) in the electrode active material is A O and the sulfur content (mass%) is A S In the case where A O and A S and are electrode active materials that satisfy the following formula. (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550
[0014] The right side of formula (1) is preferably 11.0. The right side of formula (2) is preferably 50.0. The right side of formula (3) is preferably 570. It is believed that the effect of the present invention can be more effectively achieved by satisfying stricter conditions for at least one of the formulas.
[0015] The active material preferably further contains a metal compound containing at least one metal selected from the group consisting of iron, molybdenum, vanadium and titanium.
[0016] The metal compound is preferably an iron compound.
[0017] Another embodiment of the present invention is an electrode comprising the electrode active material.
[0018] The electrode includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm ) of the electrode active material on the current collector is 2 ) is D, then D and A O and A S It is preferable that the following formula is satisfied: (4) D×(A O ×A S )>1000
[0019] It is believed that by making the product of the coating density, the oxygen content, and the sulfur content exceed a certain value, it is possible to improve the performance of the electrode and / or the battery.
[0020] The electrode includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm ) of the electrode active material on the current collector is 2 ) is D and the thickness of the metal foil is T (μm), D, T and A O and A S It is preferable that and satisfy the following formula: (5) D×(A O ×A S ) / T>60
[0021] It is believed that by ensuring that the coating density, oxygen content, sulfur content, and metal foil thickness satisfy the above formula, it is possible to improve the performance of the electrode and / or battery.
[0022] The electrode includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm ) of the electrode active material on the current collector is 2 ) is D, D is 2.50mg / cm 2 It is preferable that the range is 100 to 2000 nm.
[0023] The electrode is preferably a positive electrode.
[0024] It is believed that use of this material as a positive electrode can improve the performance of the electrode and / or battery.
[0025] Another embodiment of the present invention is a lithium ion secondary battery comprising the electrode.
[0026] The lithium ion secondary battery further comprises an electrolyte, the volume of the electrolyte being V (mL), and the coating density of the electrode active material on the current collector being V (mg / cm 2 ) is D, then D, V and A O and A S It is preferable that the following formula is satisfied: (6) D×(A O ×A S ) / V>4000
[0027] It is believed that by ensuring that the coating density, oxygen content, sulfur content, and volume of the electrolyte satisfy the above formula, it is possible to improve the performance of the electrode and / or battery.
[0028] Another embodiment of the present invention is a method for producing an electrode active material, comprising the steps of: (1) a mixing step of mixing a raw material containing cellulose and sulfur in a mass equal to or greater than the mass of the cellulose to obtain a calcined raw material; (2) a firing step of firing the firing raw material to obtain a fired product; and (3) A granulation step of pulverizing the fired product to obtain fired product particles. The method for producing an electrode active material includes the steps of:
[0029] The cellulose is preferably not chemically modified.
[0030] This is because the absence of chemical modification is believed to prevent the reaction between sulfur and cellulose from becoming insufficient due to chemical modification, and as a result, it is possible to avoid a decrease in the sulfur content.
[0031] <Definition> The term "particles" refers to a state in which the electrode active material is sufficiently fine to be suitable for mixing with other materials for the purpose of the present invention. The size of the particles constituting the electrode active material is not particularly limited as long as the above-mentioned mixing can be suitably carried out. For example, when the "particles" are expressed by a median diameter, the size can be within the range of 1 nm to 1000 μm.
[0032] "Particle size" is expressed as the median size (d50) unless otherwise specified.
[0033] "Electrode active material" refers to one of the electrode materials of a battery, and refers to a substance that is involved in the reaction that generates electricity. Electrode active materials are classified into positive electrode active materials and negative electrode active materials.
[0034] The "oxygen content in the electrode active material" is the amount (mass %) of elemental oxygen contained in the electrode active material.
[0035] The "sulfur content in the electrode active material" is the amount (% by mass) of elemental sulfur contained in the electrode active material.
[0036] The term "active material" refers to a substance that is responsible for the oxidation-reduction reaction that takes place for energy conversion in a lithium-ion secondary battery.
[0037] "Coating density" refers to the unit area (cm2) of the active material coated on the current collector. 2 ) mass (mg) per unit mass.
[0038] "Volume of electrolyte" means the total volume of the electrolyte solution, including the solute, or the solid electrolyte, in mL.
[0039] "Initial discharge capacity" refers to the second discharge capacity unless otherwise specified.
[0040] <Measurement method>
[0041] The "contents of oxygen, sulfur, etc. in the electrode active material" are measured by the methods described in the Examples. That is, the elemental amounts of carbon, hydrogen, nitrogen, and sulfur are measured by the oxygen flow combustion-infrared absorption method using a fully automatic elemental analyzer vario MICRO cube manufactured by Elementar. The elemental amount of oxygen is measured by the inert gas fusion-infrared absorption method using an oxygen / nitrogen / hydrogen analyzer EMGA-930 manufactured by Horiba, Ltd.
[0042] The "particle size distribution" is measured using a laser diffraction / scattering particle size distribution analyzer (Anton Paar's PSA1090L particle size distribution analyzer) with water as the dispersion medium.
[0043] Unless otherwise specified, the "median size" is measured as the volume-based cumulative 50% diameter (μm) in the particle size distribution.
[0044] The electrode active material, the electrode, and the lithium ion secondary battery of the present embodiment will be described below.
[0045] <Electrode active material> The electrode active material is an electrode active material composed of particles containing an organic sulfur compound, and as shown in the above formulas (1) to (3), the oxygen content (mass%) in the electrode active material A O and sulfur content (mass%) A S and exceed a predetermined value, and A O and A S The product of these electrode active materials exceeds a predetermined value.
[0046] The organic sulfur compound is a compound formed by calcining an organic compound, such as cellulose, with sulfur in a non-oxidizing atmosphere, thereby incorporating sulfur. In the present embodiment, the organic sulfur compound is not particularly limited as long as it constitutes particles and the electrode active material made of the particles satisfies the above formulas (1) to (3).
[0047] (Formula (1)~Formula (3)) The oxygen content (mass%) in the electrode active material is AO and the sulfur content (mass%) is A S In the case where A O and A S satisfies the following formula: (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550
[0048] The right side of formula (1) is preferably 10.0, more preferably 11.0, even more preferably 12.0, even more preferably 13.0, even more preferably 14.0, even more preferably 15.0, even more preferably 16.0, even more preferably 17.0, even more preferably 18.0. O The upper limit of the value is not particularly limited, but as a reference value, it can be assumed to be about 30.00.
[0049] A O can be increased by using an organic compound containing many oxygen atoms as a raw material for calcination, and conversely, can be decreased by using an organic compound containing few oxygen atoms as a raw material for calcination. An example of an organic compound containing a relatively large number of oxygen atoms is cellulose.
[0050] (Formula (2)) The right side of formula (2) is preferably 46.0, more preferably 47.0, even more preferably 48.0, even more preferably 49.0, even more preferably 50.0, even more preferably 51.0, even more preferably 52.0, even more preferably 53.0, even more preferably 54.0, even more preferably 55.0, even more preferably 56.0, even more preferably 57.0, even more preferably 58.0, even more preferably 59.0. S The upper limit of the value is not particularly limited, but as a reference value, it can be assumed to be about 70.0.
[0051] A Scan be increased by using more sulfur as a calcination raw material, and conversely, can be decreased by using less sulfur as a calcination raw material.
[0052] (Formula (3)) The right side of formula (3) is preferably 560, more preferably 570, even more preferably 600, even more preferably 650, even more preferably 700, even more preferably 750, even more preferably 800, even more preferably 830, even more preferably 840. O ×A S The upper limit is not particularly limited, but it can be assumed to be about 1500 as a reference value.
[0053] A O ×A S A O The value of and A S The values of can be adjusted accordingly.
[0054] (elements other than oxygen and sulfur) The electrode active material may contain elements other than oxygen and sulfur, such as carbon, hydrogen, nitrogen, etc.
[0055] [Carbon content] From the viewpoint of improving the performance of the electrode and / or the battery, the amount of carbon element is preferably more than 5.0 mass%, more preferably more than 10.0 mass%, and even more preferably more than 15.0 mass%, while the amount of the element is preferably less than 50.0 mass%, more preferably less than 45.0 mass%, and even more preferably less than 40.0 mass%.
[0056] [Hydrogen content] By calcination, hydrogen (H) in the organic compound reacts with sulfur to become hydrogen sulfide, which is released outside the system. Therefore, the hydrogen content of the electrode active material is preferably less than 1.0 mass%, more preferably less than 0.7 mass%, and even more preferably less than 0.5 mass%. When it is less than 1.0 mass%, there is a tendency that the calcination (sulfurization reaction) is sufficient. Therefore, in this case, the charge / discharge capacity tends to be improved.
[0057] [Nitrogen content] The amount of nitrogen element (mass%) in the electrode active material may be 0 mass% if no nitrogen source is used as the raw material. For example, if a compound containing a nitrogen atom is used as the organic compound, the nitrogen element can be detected.
[0058] (Metal element content) The electrode active material preferably further contains a metal compound containing at least one metal selected from the group consisting of iron, molybdenum, vanadium and titanium. The metal compound is preferably an iron compound. One or more kinds of the metal compounds can be used.
[0059] When the electrode active material contains a metal compound, the amount of the metal element (mass %) is preferably more than 10.0 mass %, more preferably more than 15.0 mass %, and even more preferably more than 20.0 mass %, from the viewpoint of improving the performance of the electrode and / or the battery, while the amount of the metal element is preferably less than 30 mass %, more preferably less than 25.0 mass %, and even more preferably less than 24.0 mass %. Here, when the metal compound contains multiple metal elements, the amount of the metal element means the total amount of the multiple metal elements.
[0060] (Median diameter) The electrode active material is composed of particles, and the size of the particles is suitable for the manufacture of an electrode. From the viewpoint of improving the performance of the electrode and / or battery, the preferred range of the particle size of the electrode active material is preferably a median diameter (median diameter d50) of more than 1.0 μm and less than 40.0 μm. The median diameter is more preferably more than 1.5 μm, more preferably more than 2.0 μm, and even more preferably more than 3.0 μm. The median diameter is more preferably less than 30.0 μm, more preferably less than 25.0 μm, even more preferably less than 20.0 μm, even more preferably less than 15.0 μm, even more preferably less than 10.0 μm, and even more preferably less than 8.0 μm. The median diameter can be measured by the method described in the Examples section below.
[0061] (Other Ingredients) The electrode active material of this embodiment can contain the materials described in the manufacturing method section below in the same manner as described in the same section.
[0062] <Electrode> An electrode according to one embodiment of the present invention is an electrode comprising the above-mentioned electrode active material.
[0063] The electrode according to this embodiment can be used in a lithium ion secondary battery, and the electrode can be constructed by using the materials described in the manufacturing method section below in the same manner as described in the same column. That is, when the electrode is used as a positive electrode, the conductive assistant, binder, current collector, etc. described in the manufacturing method section below can be used in the same manner as described in the same column to form a positive electrode for a lithium ion secondary battery, and when the electrode is used as a negative electrode, the conductive assistant, binder, current collector, etc. described in the manufacturing method section below can be used in the same manner as described in the same column to form a negative electrode for a lithium ion secondary battery. In this way, these explanations in the manufacturing method section below can be taken into consideration as explanations of this electrode.
[0064] The electrode of this embodiment includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm) of the electrode active material on the current collector is 2 ) is D, then D and A O and AS It is preferable that and satisfy the following formula: (4) D×(A O ×A S )>1000
[0065] (Formula (4)) The right side of formula (4) is more preferably 1500, even more preferably 1700, even more preferably 1900, even more preferably 2100, even more preferably 2200, and even more preferably 2300. Note that the higher the value of the left side of formula (4), the more preferable it is, and there is no point in setting an upper limit, but as a reference value, a value of about 5000 can be assumed.
[0066] (coating density) The coating density D (mg / cm) of the electrode active material on the electrode 2 ) is 2.50 mg / cm 2 More preferably, it is greater than 3.00 mg / cm 2 More preferably, 3.50 mg / cm 2 More preferably, 3.80 mg / cm 2 More preferably, 3.90 mg / cm 2 The higher the coating density, the better, and there is no point in setting an upper limit. However, as a reference value, 15.0 mg / cm 2 It can also be estimated to be.
[0067] (Formula (5)) The electrode of this embodiment includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm) of the electrode active material on the current collector is 2 ) is D and the thickness of the metal foil is T (μm), D, T and A O and A S It is preferable that and satisfy the following formula: (5) D×(A O ×A S ) / T>60
[0068] The right side of formula (5) is more preferably 80, even more preferably 90, even more preferably 110, even more preferably 120, and even more preferably 130. The higher the value of the left side of formula (5), the more preferable it is, and there is no point in setting an upper limit, but as a reference value, a value of about 300 can be assumed.
[0069] (Thickness of metal foil) The thickness T (μm) of the metal foil is preferably in the range of 5 μm or more, more preferably 10 μm or more, while T is preferably 40 μm or less, more preferably 30 μm or less, and further preferably 25 μm or less.
[0070] (Charge / discharge capacity) The electrode of this embodiment exhibits excellent charge / discharge capacity. 2 ) is the discharge capacity when the electrode and the battery are charged and discharged twice with a discharge end voltage of 1.0V and a charge end voltage of 3.0V after the preparation of the electrode and the battery (this is the second discharge when the first discharge, first charge, second discharge, and second charge are repeated). In the case of discharge, when the battery is discharged at a constant current (current value equivalent to 50mA per 1g of positive electrode active material), the voltage of 3.0V eventually drops to 1.0V. The total time (h) from 3.0V to 1.0V is measured and multiplied by the current (mA) applied to obtain the capacity (mAh), and the specific capacity (mAh / g) is obtained by dividing the capacity by the weight of the active material. On the other hand, in the case of charging, the voltage rises due to charging at a constant current, and when it finally reaches 3.0V, charging is completed. The same applies to the 10th and 20th discharge capacities described later.
[0071] [Initial discharge capacity (DC 2 )] Initial discharge capacity DC when the electrode of this embodiment is used as a positive electrode 2 (mAh / g) is preferably greater than 455 mAh / g. 2is more preferably more than 460mAh / g, even more preferably more than 470mAh / g, even more preferably more than 480mAh / g, even more preferably more than 490mAh / g, even more preferably more than 500mAh / g, even more preferably more than 550mAh / g. There is no particular limit to the upper limit of the initial discharge capacity, and the higher the better. Therefore, there is little meaning in mentioning the upper limit of the initial discharge capacity, but it can be assumed to be, for example, about 1000mAh / g as a reference value.
[0072] [20th discharge capacity (DC 20 )] When the electrode of this embodiment is used as a positive electrode, the discharge capacity after 20 repeated charge and discharge cycles, i.e., the 20th discharge capacity DC 20 (mAh / g) is preferably greater than 375 mAh / g. 20 is more preferably more than 400mAh / g, even more preferably more than 430mAh / g, even more preferably more than 450mAh / g, even more preferably more than 480mAh / g, even more preferably more than 490mAh / g, even more preferably more than 500mAh / g, even more preferably more than 550mAh / g. There is no particular limit to the upper limit of the discharge capacity, and the higher the better. Therefore, there is little meaning in mentioning the upper limit of the discharge capacity, but it can be assumed to be, for example, about the value of the initial discharge capacity or about 900mAh / g as a reference value.
[0073] In addition, the second and twentieth discharge capacities when the electrode of this embodiment is used as a positive electrode are determined by the configuration of the positive electrode, if the negative electrode and electrolyte are within the technical common sense that can be used as a lithium ion secondary battery (i.e., Li is not depleted) and the performance related to the discharge capacity of the positive electrode is fully exhibited, and the measurement is performed in such a way that the performance related to the discharge capacity of the positive electrode is fully exhibited. For example, for the negative electrode, it is sufficient to use lithium in an amount (molar amount) preferably 2 times or more, more preferably 5 times or more, even more preferably 10 times or more, and even more preferably 50 times or more than the amount of sulfur (molar amount) in the positive electrode. Also, for example, for the electrolyte, if the amount of electrolyte (microliters) is preferably 10 times or more, more preferably 20 times or more, and even more preferably 50 times or more than the amount of sulfur (mg) in the positive electrode, the discharge capacity of the positive electrode can be fully exhibited, leading to a long life of the battery. On the other hand, considering the energy density of the battery, it is preferable that the amount of electrolyte is small. For example, the amount of electrolyte (microliters) is preferably 5 times or less, more preferably 3 times or less, and even more preferably 1 time or less, relative to the amount of sulfur (mg) in the positive electrode. Here, the volume V (mL) of the electrolyte means the total volume of the electrolyte solution including the solute. The electrolyte may be in the form of an electrolyte solution or a solid (solid electrolyte), or may be a combination of both.
[0074] (Application) The electrode of the present embodiment can be used as a positive electrode or a negative electrode of a lithium ion secondary battery, and is preferably used as a positive electrode of a lithium ion secondary battery.
[0075] <Lithium-ion secondary battery> A lithium ion secondary battery according to one embodiment of the present invention is a lithium ion secondary battery comprising the above-described electrode.
[0076] The lithium ion secondary battery of this embodiment can be constructed by using the materials described in the manufacturing method column below in the same manner as described in the same column. That is, when the above electrode is used as a positive electrode, a lithium ion secondary battery can be constructed by using the negative electrode, electrolyte, separator, etc. described in the manufacturing method column below in the same manner as described in the same column. On the other hand, when the above electrode is used as a negative electrode, a lithium ion secondary battery can be constructed by using the positive electrode, electrolyte, separator, etc. described in the manufacturing method column below in the same manner as described in the same column. In this way, these explanations in the manufacturing method column below can be taken into consideration as explanations of this lithium ion secondary battery.
[0077] (Formula (6)) The lithium ion secondary battery of the present embodiment further comprises an electrolyte, the volume of the electrolyte being V (mL), and the coating density of the electrode active material on the current collector being V (mg / cm 2 ) is D, then D, V and A O and A S It is preferable that and satisfy the following formula (6). (6) D×(A O ×A S ) / V>4000
[0078] The right side of formula (6) is more preferably 4500, even more preferably 5000, even more preferably 5500, even more preferably 6000, even more preferably 7000, even more preferably 7500, and even more preferably 8000. The higher the value of the left side of formula (6), the more preferable it is, and there is no point in setting an upper limit, but as a reference value, a value of about 20000 can be assumed.
[0079] (volume of electrolyte V) The volume V (mL) range of the electrolyte is not generally specified because it may vary depending on the size of the battery, and the minimum amount that draws out the performance of the electrode active material and operates sufficiently as a battery may be used. For example, as a reference value only, in the case of a coin-type battery presented in the examples, it is preferably 0.1 mL or more, more preferably 0.12 mL or more, and even more preferably 0.15 mL or more. On the other hand, the V is preferably 0.40 mL or less, more preferably 0.30 mL or less, even more preferably 0.28 mL or less, and even more preferably 0.25 mL or less.
[0080] (Application) The lithium ion secondary battery of the present embodiment is useful as a lithium ion secondary battery with improved overall performance in terms of charge / discharge capacity and capacity retention rate, and can be used as a battery for next-generation clean energy automobiles, such as hybrid electric vehicles (HEVs), electric vehicles (EVs), and plug-in hybrid electric vehicles (PHEVs), as well as for portable information terminals such as smartphones and notebook personal computers, portable electronic devices such as music players and digital cameras, and medical devices.
[0081] <Production method> The electrode active material, the electrode, and the method for producing the lithium ion secondary battery according to this embodiment will be described below in order.
[0082] (Production of electrode active material) The electrode active material of the present embodiment can be produced by various methods. For example, the following method can be mentioned as a method using cellulose as the organic compound serving as a raw material.
[0083] That is, the electrode active material of this embodiment is (1) a mixing step of mixing a raw material containing cellulose and sulfur in a mass equal to or greater than the mass of the cellulose to obtain a calcined raw material; (2) a firing step of firing the firing raw material to obtain a fired product; and (3) A granulation step of pulverizing the fired product to obtain fired product particles. It can be produced by a production method including the steps of:
[0084] [Raw materials] The raw materials used as the firing raw materials will be described below.
[0085] <Cellulose> Cellulose (Cellulose, Cell-OH, Ce) is a natural polymer that is the main component of the cell walls and fibers of plant cells. 12 H 20 O 10 ) n Cellulose has the following chemical structural formula: In this chemical structural formula, n, which indicates the average number of repetitions, is a number of 1 or more, preferably 10 to 10,000, and more preferably 50 to 2,000.
[0086] [ka]
[0087] As is clear from the above chemical structure, cellulose has multiple hydroxyl groups, and therefore exists as an esterified form in which all or part of the hydroxyl groups are esterified by an esterifying agent. As the esterifying agent, there is no particular limitation as long as it can provide a carboxyl group to the hydrophilic group of cellulose, and various esterifying agents can be used, for example, a carboxylic acid compound can be used, and for example, a compound having two or more carboxyl groups or an acid anhydride of a compound having two or more carboxyl groups can be used. In this embodiment, cellulose also includes such esterified forms.
[0088] Cellulose as a plant material is composed of cellulose fibers of 20 to 40 μm, and these cellulose fibers are bundles of cellulose microfibrils, and further, cellulose microfibrils are bundles of cellulose molecular chains. Therefore, it is preferable to defibrate such cellulose as a plant material before use.
[0089] There are mechanical and chemical defibration processes, and either of these can be used in this embodiment. Here, examples of mechanical defibration processes include the high-pressure homogenizer method, the microfluidizer method (opposed jet collision method), the grinder method, the ball mill crushing method, the bead mill crushing method, and the freeze crushing method. Among these, the freeze crushing method is preferred. Examples of chemical defibration processes include the TEMPO method, the phosphoric acid esterification method, the phosphorous acid esterification method, the carboxymethylation method, the sandating method, the sulfonation method, the enzyme hydrolysis method, the acid hydrolysis method, and the ionic liquid selective dissolution method.
[0090] When cellulose is defibrated by a mechanical defibration treatment, it is not chemically modified, but when defibrated by a chemical defibration treatment, it is chemically modified. In the present embodiment, from the viewpoint of improving the performance of the electrode and / or the battery, cellulose that has been defibrated by a mechanical defibration treatment and has not been chemically modified is preferable.
[0091] Prior to the fiberization treatment, the cellulose is preferably subjected to a chemical or enzymatic pretreatment.
[0092] One or more types of cellulose can be used.
[0093] Sulfur As the sulfur, any of various forms such as powdered sulfur, insoluble sulfur, precipitated sulfur, colloidal sulfur, etc. can be used, among which precipitated sulfur and colloidal sulfur are preferred. One or more types of sulfur can be used.
[0094] From the viewpoint of improving the performance of the electrode and / or battery, the sulfur content in the calcination raw material is preferably 100 parts by mass or more, more preferably more than 100 parts by mass, more preferably more than 200 parts by mass, more preferably more than 200 parts by mass, and even more preferably more than 300 parts by mass, relative to 100 parts by mass of cellulose. On the other hand, there is no particular upper limit for the sulfur content, but it is preferably less than 1000 parts by mass, more preferably less than 900 parts by mass, more preferably less than 800 parts by mass, more preferably less than 700 parts by mass, more preferably less than 600 parts by mass, more preferably less than 500 parts by mass, and even more preferably 400 parts by mass or less. Being less than 1000 parts by mass tends to be advantageous in terms of cost.
[0095] Any of the various sulfur allotropes can be used. However, S, which is solid at room temperature and pressure, is preferred. 8 It is preferable that it contains sulfur, and S 8 It is more preferable that the sulfur is an elemental substance.
[0096] ≪Raw metal compound≫ When the electrode active material further contains a metal compound containing at least one metal selected from the group consisting of iron, molybdenum, vanadium, and titanium, a raw material metal compound can be further used as a raw material for firing. Examples of the raw material metal compound include the following raw material metal compounds. It is preferable to use a raw material iron compound as the raw material metal compound.
[0097] {Raw material iron compound} The raw iron compound may be an iron compound containing divalent or trivalent iron ions, but is not particularly limited as long as it decomposes during firing and reacts with sulfur to generate iron disulfide, and various compounds may be used. Examples of the raw iron compound include iron acid salts and iron complexes. Examples of iron acid salts include both organic iron acid salts and inorganic iron acid salts. On the other hand, examples of iron complexes include neutral iron complexes and salts of iron complex ions (iron complex salts). Of these, organic iron acid salts, inorganic iron acid salts, and neutral iron complexes are preferred. One or more iron compounds may be used.
[0098] Examples of organic acid salts of iron include divalent iron (Fe 2+ ) and organic acid salts, and trivalent iron (Fe 3+ Among these, the salts of divalent iron and organic acids are preferred. Organic acids include those with a carboxyl group (-COOH) and those with a sulfo group (-SO 3 H), but those having a carboxyl group are preferred. Specific examples of organic acids include fatty acids, oxalic acid, tartaric acid, citric acid, malic acid, succinic acid, etc. Specific examples of fatty acids include those having 1 to 6 carbon atoms, such as acetic acid, propionic acid, and butyric acid. Of these, acetic acid, oxalic acid, etc. are preferred. Preferred examples of organic acid salts of iron include iron(II) acetate and iron(II) oxalate, etc. These may be hydrates. One or more types of organic acid salts of iron can be used.
[0099] Examples of inorganic salts of iron include divalent iron (Fe 2+ ) and salts with inorganic acids, and trivalent iron (Fe 3+ ) and an inorganic acid. Specific examples of inorganic acids include hydrochloric acid, sulfuric acid, and nitric acid. Of these, nitric acid is preferred. Preferred examples of inorganic acid salts of iron include iron chloride (II), iron chloride (III), iron sulfate (II), iron sulfate (III), iron nitrate (II), and iron nitrate (III). These may be hydrates. One or more inorganic acid salts of iron may be used.
[0100] As an example of an iron complex, divalent iron (Fe 2+ ) complexes and trivalent iron (Fe 3+ ) complexes. The iron complex may be in the form of a neutral complex or a complex salt. The ligand coordinated to the iron ion is not particularly limited, and examples thereof include halogen atoms such as chlorine atoms and bromine atoms, cyano groups, dicyclopentadienyl groups, and N,N'-bis(salicylidene)ethylenediamine. Examples of iron complexes include potassium hexacyanidoferrate(II) ([Fe(CN) 6 ]K 4 ), potassium hexacyanidoferrate(III) ([Fe(CN) 6 ]K 3 ), sodium tetrachloroferrate(III) ([FeCl 4 ]Na), dicyclopentadienyl iron (II) (ferrocene), N,N'-bis (salicylidene) ethylenediaminato iron (III) chloride, etc. One or more kinds of iron complexes can be used.
[0101] <Raw material molybdenum compound> Examples of the raw molybdenum compound include molybdenum trioxide (VI), sodium molybdate (VI), hexaammonium heptamolybdate (VI), diammonium molybdate (VI), calcium molybdate (VI), molybdic acid (VI), phosphomolybdic acid (VI), molybdenum disulfide (VI), etc. One or more types of molybdenum compounds can be used.
[0102] <Raw material vanadium compound> Examples of the raw vanadium compound include vanadium pentoxide (V), ammonium metavanadate (V), vanadium oxytrichloride (V), sodium metavanadate (V), potassium vanadate (V), sodium vanadate (V), vanadium tetrachloride (IV), vanadium oxysulfate (IV), vanadium oxydichloride (IV), vanadium oxide (IV), vanadium trichloride (IV), vanadium oxide (III), hexavanadium trioxide (IV, V), etc. One or more vanadium compounds can be used.
[0103] {Raw titanium compound} Examples of the raw titanium compound include titanium oxide, titanium dioxide, titanium trioxide, titanium tetrachloride, etc. One or more types of titanium compounds can be used.
[0104] <Content of raw metal compounds> From the viewpoint of improving the performance of the electrode and / or the battery, the content of the raw material metal compound in the calcination raw material is preferably 50 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of cellulose. The content is more preferably more than 50 parts by mass, even more preferably more than 60 parts by mass, even more preferably more than 70 parts by mass, and even more preferably more than 75 parts by mass. On the other hand, the content is more preferably less than 250 parts by mass, even more preferably less than 200 parts by mass, even more preferably less than 150 parts by mass, and even more preferably 100 parts by mass or less.
[0105] <Median diameter of raw metal compound> It is preferable that the raw metal compound is crushed in advance when used as a firing raw material. The median diameter (d50) of the metal compound is preferably 12.00 μm or less, more preferably. The median diameter is preferably 10.00 μm or less, more preferably 8.00 μm or less, even more preferably 6.00 μm or less, even more preferably 4.00 μm or less, and even more preferably 3.00 μm or less. On the other hand, there is no particular restriction on the lower limit of the median diameter, but it is usually about 0.10 μm or more, may be about 1.00 μm or about 2.00 μm. The median diameter can be measured by the above-mentioned method.
[0106] Specific surface area of raw metal compound The specific surface area of the raw metal compound is 1.0 m 2 / g or more, and more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, more preferably 4.0m 2 / g or more, more preferably 4.5m 2 On the other hand, there is no particular upper limit on the specific surface area, but it is usually 40.0 m 2 / g or less, and 2 / g or less, and 2 The specific surface area can be measured by a fully automatic specific surface area measuring device, Macsorb (HM-model 1201, manufactured by Mountec Co., Ltd.).
[0107] The raw metal compound having the above-mentioned median diameter or specific surface area can be prepared by a conventional method, for example, by pulverizing the raw metal compound with a pulverizer. As such a pulverizer, for example, a pulverizer manufactured by Japan Analytical Industry Co., Ltd. (e.g., JFC-2000, etc.) can be used.
[0108] Other ingredients The raw materials may optionally contain other materials commonly used in this field, such as carbon materials.
[0109] Carbon Materials In the electrode active material of this embodiment, the carbon material preferably has a graphite structure. In addition, the carbon material is preferably conductive. Examples of the carbon material include porous carbon materials such as activated carbon, graphite, carbon black, acetylene black, and ketjen black, as well as carbon fibers such as carbon fibers, vapor-grown carbon fibers (VGCF), carbon nanotubes (CNT), and carbon nanofibers, and nanocarbon materials in a form other than carbon fibers such as graphene and fullerene. Among these, carbon fibers such as carbon fibers, vapor-grown carbon fibers (VGCF), CNT, and carbon nanofibers are preferred, and CNT is particularly preferred. One or more types of carbon materials can be used.
[0110] When the carbon material is carbon fiber, the form of the fibers constituting the carbon fiber is preferably such that the average fiber length is a predetermined value or more and the average fiber diameter is a predetermined value or less from the viewpoint of improving the performance of the electrode and / or the battery. This is because it is considered that the conductivity of the electrode active material can be improved. The average fiber length is preferably more than 1 μm, more preferably more than 1.5 μm, and even more preferably 2 μm or more. There is no particular limit to the upper limit of the average fiber length, and it may be 100 μm, 50 μm, or 20 μm. In addition, the average fiber diameter is preferably less than 100 nm, more preferably less than 50 nm, and even more preferably less than 10 nm. There is no particular limit to the lower limit of the average fiber diameter, but it is usually about 1 nm.
[0111] The aspect ratio of the carbon material is preferably greater than 10, more preferably greater than 100, and even more preferably greater than 1,000; and is preferably less than 100,000, more preferably less than 50,000, and even more preferably less than 10,000.
[0112] From the viewpoint of the effect of the present invention, the carbon material has a specific surface area of 400 m 2 / g or more, and 2 The specific surface area is preferably 500 m 2 / g or more is more preferable, and 600m 2 On the other hand, the specific surface area is preferably 2000 m 2 / g or less is more preferable, and 1800m 2 The specific surface area is measured by the BET multipoint method.
[0113] From the viewpoint of the effect of the present invention, the carbon material preferably has a G / D ratio of 10 or more. The G / D ratio is more preferably 20 or more, more preferably 30 or more, and even more preferably 40 or more. On the other hand, there is no particular limit on the upper limit of the G / D ratio, but if it is 50, it can be said that the carbon material has very few defects. Here, the G / D ratio is the ratio of a representative Raman shift peak in the Raman spectrum of the carbon material, and more specifically, the ratio of the G-band peak derived from the graphite structure to the D-band peak derived from defects. The Raman spectrum was measured using a RAMANTouch (excitation wavelength λ=532 nm, grating: 1200 gr / mm, resolution: 1.2 cm-1) manufactured by Nanophoton Co., Ltd.
[0114] From the viewpoint of the effect of the present invention, the carbon material preferably has a metal impurity content of 5 mass% or less. The metal impurity content is preferably 3 mass% or less, more preferably 2 mass% or less, and even more preferably 1 mass% or less. The smaller the metal impurity content, the better, and for example, 0.1 mass% is a sufficiently small amount of metal impurities. Note that the metal impurities referred to here refer to metal elements other than iron, molybdenum, vanadium, and titanium.
[0115] From the viewpoint of improving the performance of the electrode and / or the battery, the content of the carbon material in the calcination raw material is preferably less than 5 parts by mass relative to 100 parts by mass of the cellulose. The content is more preferably less than 1 part by mass, and even more preferably less than 0.5 parts by mass. On the other hand, the content is preferably more than 0.05 parts by mass, more preferably more than 0.07 parts by mass, and even more preferably 0.10 parts by mass or more.
[0116] (manufacturing process) [Mixing process (1)] The mixing step is a step of mixing a raw material containing cellulose and sulfur in a mass equal to or greater than the mass of the cellulose to obtain a calcined raw material.
[0117] The above-mentioned mixing is not particularly limited as long as the method is such that these components are sufficiently mixed, and can be carried out by a conventional method. In this embodiment, for example, a method of mixing raw materials containing cellulose in a powder state and sulfur in a powder state having a mass equal to or greater than the mass of the cellulose as they are using a blender or the like can be mentioned. In addition, when an optional component such as a raw metal compound or a carbon material is added to the raw material, the optional component may be mixed together with the raw material using a blender or the like.
[0118] Here, the powder refers to a state in which each solid raw material is sufficiently finely divided to a degree suitable for mixing under the purpose of the present invention. The size of each particle constituting the powder is not particularly limited as long as the mixing is carried out suitably, but is usually, for example, in the range of 1 μm or more and 40 μm or less. From the viewpoint of improving the performance of the electrode and / or battery, the size of the particles is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and preferably 30 μm or less, even more preferably 20 μm or less, even more preferably 15 μm or less, even more preferably 10 μm or less, in terms of the median diameter. The median diameter can be measured by the above-mentioned method.
[0119] The raw material thus obtained may be used as it is in the next firing step, or may be formed into pellets, if desired, and then used in the next step.
[0120] [Firing process (2)] The calcination step is a step of calcining the calcination raw material obtained above to obtain a calcined product. Calcination can be performed by a conventional method, for example, by heating the calcination raw material at a predetermined temperature increase rate until it reaches a predetermined temperature, maintaining the temperature at the predetermined temperature for a predetermined time, and then naturally cooling it.
[0121] <Non-oxidizing atmosphere> The firing is preferably carried out in a non-oxidizing atmosphere. The non-oxidizing atmosphere refers to an atmosphere that is substantially free of oxygen, and is adopted to suppress oxidative deterioration of the components and excessive thermal decomposition. Specifically, the non-oxidizing atmosphere refers to an inert gas atmosphere such as nitrogen or argon, a sulfur gas atmosphere, an ammonia gas atmosphere, etc. Therefore, the firing can be suitably carried out, for example, in a quartz tube under an inert gas atmosphere.
[0122] <Heating rate> The heating rate is preferably, for example, within the range of 50° C. / h or more and 500° C. / h or less. The heating rate is preferably 80° C. / h or more, more preferably 100° C. / h or more, and even more preferably 120° C. / h or more. On the other hand, the heating rate is more preferably 400° C. / h or less, even more preferably 300° C. / h or less, and even more preferably 200° C. / h or less. When the heating rate is within such a range, it tends to be easier to achieve the purpose of improving the charge / discharge capacity and cycle characteristics.
[0123] <Baking temperature and time> The calcination temperature is the temperature after the temperature rise of the raw material is completed, and is maintained for a certain period of time for calcination of the raw material. The temperature is preferably in the range of more than 250°C and less than 550°C. By being more than 250°C, the sulfurization reaction tends to be avoided from being insufficient, and the charge / discharge capacity of the target product tends to be prevented from decreasing. On the other hand, by being less than 550°C, the decomposition of the raw material tends to be prevented, and the decrease in yield and the decrease in charge / discharge capacity tend to be prevented. The temperature is more preferably more than 270°C, more preferably more than 290°C, and even more preferably 300°C or more. On the other hand, the temperature is more preferably less than 500°C, more preferably less than 470°C, and even more preferably 450°C or less.
[0124] When a raw material metal compound is used as a raw material, the calcination temperature in the calcination step is preferably higher than the temperature at which the raw material metal compound thermally decomposes, from the viewpoint of improving the performance of the electrode and / or battery.
[0125] The time for maintaining the calcination temperature may be appropriately set depending on the type of raw material, the calcination temperature, etc., but is preferably, for example, 0.5 hours or more and 6 hours or less. By setting the time to 0.5 hours or more, the calcination tends to proceed sufficiently, and by setting the time to 6 hours or less, excessive thermal decomposition of the components tends to be prevented. The time is more preferably 0.6 hours or more, and even more preferably 0.7 hours or more. On the other hand, the time is more preferably 4 hours or less, and even more preferably 2 hours or less.
[0126] ≪Device≫ The calcination can be carried out, for example, by a muffle furnace (FIG. 1), or can be carried out by using a continuous apparatus such as a twin-screw extruder. When a continuous apparatus is used, there is an advantage that the sulfur-based electrode active material can be produced continuously by a series of operations, such as kneading, pulverizing, and mixing the raw materials and calcining them in the apparatus.
[0127] A muffle furnace (Figure 1) is a furnace partitioned by a hot plate or the like so that the heat source (heater) is not exposed inside the furnace in order to prevent contamination of samples. In Figure 1, a muffle furnace 1 has a heater 2 at the bottom of the furnace, which is partitioned by a hot plate. A lid 3 is installed on the front side of the furnace (the left end side in the figure), and the furnace is structured so that an atmosphere of inert gas 4 can be maintained inside the furnace. A thermocouple (not shown) is attached to the lid, and the temperature inside the furnace during sintering can be measured. Inside the furnace, two trays 5 and 6, which are rectangular parallelepiped reaction vessels made of stainless steel and used to sinter the raw materials, are installed on the upper and lower levels.
[0128] Gas (e.g., an inert gas such as argon (Ar) gas) can be continuously supplied to and discharged from the inside of the furnace through a gas inlet pipe 7 and a gas exhaust pipe 8. The gas exhaust pipe 8 is connected to a trap tank 10 containing an aqueous sodium hydroxide solution 9, and exhaust air attempting to exit from the muffle furnace 1 through the gas exhaust pipe 8 to the outside passes through the aqueous sodium hydroxide solution 9 in the trap tank 10 before being discharged to the outside. Therefore, even if the exhaust air contains hydrogen sulfide gas generated by the reaction, it is neutralized with the aqueous sodium hydroxide solution and removed from the exhaust air.
[0129] [Residue removal process] The residue removal step is a step of removing residues such as unreacted sulfur that is formed when the sulfur sublimed during the firing cools and precipitates from the fired product. Since these residues are a factor in reducing cycle characteristics, it is desirable to remove as much of the residues as possible when they exist. The removal of the residues can be carried out, for example, by subjecting the fired product to a conventional method such as reduced pressure heating drying, hot air drying, or solvent washing.
[0130] [Crushing process (3)] The pulverization step is a step of pulverizing the sintered product to obtain particles of the sintered product. The sintered product is preferably pulverized to obtain particles of a size suitable for the manufacture of an electrode. The preferred size range of the particles of the electrode active material is as described above.
[0131] The pulverization can be carried out by a conventional method, for example, by subjecting the mixture to a pulverization treatment under predetermined conditions using a pulverizer such as a cutter mill or a jet mill. The pulverization conditions vary depending on the mill used, but for example, when a cutter mill (e.g., Free Speed Mill, FS-20, manufactured by Labnect Co., Ltd.) is used, the treatment can be carried out at a rotation speed of 20,000 rpm to 30,000 rpm for 1 second to 30 seconds. In addition, when a dry jet mill (e.g., Nano Jet Mizer, NJ-30, manufactured by Aisin Nano Technologies Co., Ltd.) is used, the treatment can be carried out at a treatment speed of 1 g / min to 3 g / min and a pulverization pressure of 0.5 MPa to 2.0 MPa.
[0132] The particles of the pulverized fired product obtained above may be classified as desired to make the particle size of the particles uniform. Classification can be carried out, for example, using a sieve with a desired mesh size.
[0133] In the firing method using the twin-screw extruder described above, the electrode active material can be produced and at the same time, the produced electrode active material can be pulverized into particles by shearing during kneading.
[0134] (Manufacturing electrodes for lithium-ion secondary batteries) Using the electrode active material obtained above, a lithium ion secondary battery electrode having an electrode active material layer containing the electrode active material can be produced by a conventional method. That is, the electrode can be obtained in the same manner as in the production of a general lithium ion secondary battery electrode, except that the electrode active material is used as the active material.
[0135] [When the electrode active material is used as a positive electrode active material] The positive electrode for lithium ion secondary batteries can be prepared in the same manner as the positive electrode for general lithium ion secondary batteries, except that the above-mentioned electrode active material is used as the positive electrode active material. For example, the positive electrode can be prepared by mixing the electrode active material with a conductive assistant, a binder, and a solvent to prepare a paste-like positive electrode material, applying the positive electrode material to a current collector, and then drying the same. In addition, as another method, the positive electrode can also be prepared by kneading the electrode active material with a conductive assistant, a binder, and a small amount of solvent using a mortar or the like, forming it into a film, and then pressing it onto a current collector using a press or the like.
[0136] <Conductive assistant> Examples of the conductive assistant include vapor grown carbon fiber (VGCF), carbon powder, carbon black (CB), acetylene black (AB), ketjen black (KB), graphite, and fine powder of metals such as aluminum and titanium that are stable at the positive electrode potential. In addition, the conductive assistant may be one of the above carbon materials that is conductive. These conductive assistants may be used alone or in combination.
[0137] <Binder> Examples of binders include polyvinylidene difluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyimide (PI), polyamide-imide (PAI), carboxymethyl cellulose (CMC), polyvinyl chloride (PVC), acrylic resin, methacrylic resin (PMA), polyacrylonitrile (PAN), modified polyphenylene oxide (PPO), polyethylene oxide (PEO), polyethylene (PE), polypropylene (PP), etc. These binders can be used alone or in combination of two or more.
[0138] <Solvent> Examples of the solvent include N-methyl-2-pyrrolidone, N,N-dimethylformaldehyde, alcohol, hexane, water, etc. These solvents can be used alone or in combination of two or more.
[0139] ≪Blend amount≫ The amounts of the materials constituting the positive electrode are not particularly limited, but it is preferable to mix, for example, 2 to 100 parts by mass of a conductive assistant, 2 to 50 parts by mass of a binder, and an appropriate amount of a solvent with respect to 100 parts by mass of an electrode active material.
[0140] <Current collector> As the current collector, one generally used for a positive electrode for a lithium ion secondary battery may be used. For example, the current collector may be made of metal foil such as aluminum foil, aluminum mesh, punched aluminum sheet, aluminum expand sheet, stainless steel foil, stainless steel mesh, punched stainless steel sheet, stainless steel expand sheet, foamed nickel, nickel nonwoven fabric, copper foil, copper mesh, punched copper sheet, copper expand sheet, titanium foil, titanium mesh, carbon nonwoven fabric, carbon woven fabric, etc. Among these, a current collector containing a metal foil is preferred. One type of current collector may be used, or two or more types may be used in combination. The surface of the current collector may be coated with carbon or the like. A specific example of such a current collector whose surface is coated with carbon or the like is, for example, carbon-coated aluminum foil. In this case, the current collector includes a carbon-coated portion.
[0141] [When the electrode active material is used as the negative electrode active material] The negative electrode for lithium ion secondary batteries can be prepared in the same manner as a general negative electrode for lithium ion secondary batteries, except that the above-mentioned electrode active material is used as the negative electrode active material. For example, the negative electrode can be prepared by mixing the electrode active material with a conductive assistant, a binder, and a solvent to prepare a paste-like negative electrode material, applying the negative electrode material to a current collector, and then drying the paste. In addition, as another method, the negative electrode can also be prepared by kneading the electrode active material with a conductive assistant, a binder, and a small amount of solvent using a mortar or the like, forming it into a film, and then pressing the film onto a current collector using a press or the like.
[0142] The conductive assistant, binder and solvent can be the same as those used in the above case where the electrode active material is used as the positive electrode active material, and the current collector can also be the same as those used in the above case.
[0143] (manufacturing lithium-ion secondary batteries) The lithium ion secondary battery of this embodiment can be manufactured in the same manner as in the manufacture of a general lithium ion secondary battery, except that the lithium ion secondary battery electrode obtained above is used.
[0144] [When the electrode active material is used as a positive electrode active material] The lithium ion secondary battery of this embodiment can be produced in accordance with a conventional method by using a positive electrode containing the above-mentioned electrode active material (positive electrode active material), a negative electrode, an electrolyte, and, if desired, components such as a separator.
[0145] ≪Negative electrode≫ As the negative electrode material, known metallic lithium, carbon-based materials such as graphite, silicon-based materials such as silicon thin film, and alloy-based materials such as copper-tin and cobalt-tin can be used. When a material that does not contain lithium is used as the negative electrode material, for example, a carbon-based material, a silicon-based material, an alloy-based material, etc. among the above-mentioned negative electrode materials, it is advantageous in that a short circuit between the positive and negative electrodes due to the generation of dendrites is unlikely to occur. However, when these lithium-free negative electrode materials are used in combination with the positive electrode of this embodiment, neither the positive electrode nor the negative electrode contains lithium. For this reason, a lithium pre-doping process is required in which lithium is inserted in advance into either or both of the negative electrode and the positive electrode. The pre-doping method of lithium may be according to a known method. For example, when doping lithium into the negative electrode, a method of inserting lithium by an electrolytic doping method in which a half cell is assembled using metallic lithium as the counter electrode and lithium is electrochemically doped, or a method of inserting lithium by a pasting pre-doping method in which a metallic lithium foil is pasted on the electrode and then left in an electrolyte solution to dope the lithium by utilizing the diffusion of lithium into the electrode, can be mentioned. In addition, the above-mentioned electrolytic doping method can be used when pre-doping the positive electrode with lithium. As the negative electrode material that does not contain lithium, silicon-based materials, which are high-capacity negative electrode materials, are particularly preferred, and among them, thin-film silicon, which has a thin electrode thickness and is advantageous in terms of capacity per volume, is more preferred.
[0146] ≪Electrolyte≫ The electrolyte compensates for the charge generated by the release of electrons to an external circuit accompanying the oxidation / reduction of the electrode active material at the positive and negative electrodes, by the flow of ions. As the electrolyte for use in a lithium ion secondary battery, an electrolyte obtained by dissolving an alkali metal salt in an organic solvent can be used. As the organic solvent, it is preferable to use at least one type selected from non-aqueous solvents such as dimethoxyethane, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl ether, γ-butyrolactone, and acetonitrile. As the electrolyte, Li(FSO 2 ) 2 N, LiPF 6 , LiBF 4, LiAsF 6 , LiCF 3 SO 3 , LiI, LiClO 4 etc. can be used. The concentration of the electrolyte may be about 0.5 mol / L to 5.0 mol / L. The electrolyte is not limited to a liquid state. For example, when the lithium ion secondary battery is a lithium polymer secondary battery, the electrolyte is in a solid state (for example, in a polymer gel state).
[0147] <Separator> The lithium ion secondary battery may include a separator and other components in addition to the above-mentioned negative electrode, positive electrode, and electrolyte. The separator is interposed between the positive electrode and the negative electrode, and allows the movement of ions between the positive electrode and the negative electrode, and prevents internal short-circuiting between the positive electrode and the negative electrode. If the lithium ion secondary battery is a sealed type, the separator is also required to have a function of retaining the electrolyte. As the separator, it is preferable to use a thin, microporous or nonwoven membrane made of polyethylene, polypropylene, polyacrylonitrile, aramid, polyimide, cellulose, glass, or the like.
[0148] ≪Shape≫ The shape of the lithium ion secondary battery is not particularly limited, and it can be in various shapes such as a cylindrical type, a stacked type, a coin type, a laminated type, and a button type.
[0149] [When the electrode active material is used as the negative electrode active material] The lithium ion secondary battery of this embodiment can be produced in accordance with a conventional method by using a negative electrode containing the above-mentioned electrode active material (negative electrode active material), a positive electrode, an electrolyte, and, if desired, components such as a separator.
[0150] ≪Positive electrode≫ The positive electrode material is not particularly limited as long as it is, for example, a transition metal oxide or solid solution oxide containing lithium, or a substance capable of electrochemically absorbing and releasing lithium ions. Examples of transition metal oxides containing lithium include LiCoO 2 Li·Co based composite oxides such as LiNi x Coy Mn z O 2 Li·Ni·Co·Mn-based composite oxides such as LiNiO 2 Li·Ni composite oxides such as LiMn 2 O 4 Examples of the solid solution oxide include Li·Mn-based composite oxides such as Li a Mn x Co y Ni z O 2 (1.150≦a≦1.430, 0.450≦x≦0.600, 0.100≦y≦0.150, 0.200≦z≦0.280), LiMn x Co y Ni z O 2 (0.300≦x≦0.850, 0.100≦y≦0.300, 0.100≦z≦0.300), LiMn 1.5 Ni 0.5 O 4 These compounds may be used alone or in combination of two or more.
[0151] <Other> The electrolyte, separator, and shape of the lithium ion secondary battery can be the same as those in the above-mentioned case where the electrode active material is used as the positive electrode active material. EXAMPLES
[0152] The present invention will be described based on examples, but the present invention is not limited to only the examples.
[0153] The various chemicals used in the Examples and Comparative Examples are listed below. The various chemicals were purified according to conventional methods as necessary.
[0154] <Materials used in the test> Cellulose: Cellulose (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., white powder, passing 38 μm (400 mesh)) Diene rubber: high cis-butadiene rubber (UBEPOL (registered trademark) BR150L manufactured by UBE Corporation, cis content (amount of cis-1,4-bonded butadiene units): 98% by mass) PP: Polypropylene (available from Sigma-Aldrich, catalog number 428116, melting point: 157°C) Cross-linked PMMA: Cross-linked polymethyl methacrylate (Techpolymer MB30X-8 manufactured by Sekisui Chemical Co., Ltd., a spherical acrylic resin consisting of methyl methacrylate and ethylene glycol dimethacrylate copolymer, particle size: 8 μm) Sulfur: Precipitated sulfur manufactured by Tsurumi Chemical Industry Co., Ltd.
[0155] Manufacturing example 1 (grinding of raw materials) Before being used as raw materials, each of the cellulose and polypropylene was ground in advance for 10 minutes using a freeze grinder (JFC-2000 manufactured by Japan Analytical Industry Co., Ltd.).
[0156] <Preparation of electrode active material> (Mixing process) The raw materials were charged according to the compounding ratios shown in the table below and mixed using a blender (LAB MILL manufactured by Osaka Chemical Co., Ltd.) to obtain a raw material to be fired.
[0157] (Firing process) The raw materials were fired in a muffle furnace (Fig. 1). The muffle furnace in Fig. 1 was as described above.
[0158] First, the atmosphere in the muffle furnace was replaced with Ar gas three times using a vacuum pump while the raw material to be fired was placed in a tray, which was a stainless steel reaction vessel. Then, Ar gas was continuously supplied from the gas inlet tube at a flow rate of 100 mL / min, and 30 minutes after the start of supply, heating of the muffle furnace was started. The temperature was increased at a rate of 5°C / min, and when the temperature of the raw material to be fired reached the firing temperature shown in Table 1, the temperature was maintained while performing heat treatment for 45 minutes. Next, the temperature of the fired product was naturally cooled to 25°C under an Ar gas atmosphere while adjusting the flow rate of Ar gas, and then the fired product was taken out of the muffle furnace.
[0159] (Removal of unreacted sulfur) In order to remove the unreacted sulfur (free elemental sulfur) remaining in the product after the firing process, the following process was carried out. That is, the fired product was crushed in a mortar, and the crushed product was placed in a glass tube oven and heated at 290°C for 3 hours while suctioning under vacuum to obtain an electrode active material from which the unreacted sulfur had been removed (or which contained only a trace amount of unreacted sulfur). The heating rate was 10°C / min.
[0160] (Crushing process) The calcined product from which the unreacted sulfur had been removed was pulverized using a cutter mill (LAB MILL manufactured by Osaka Chemical Co., Ltd.).
[0161] (Classification work) In order to remove coarse particles from the pulverized fired product, the product was classified using a 32 μm mesh stainless steel sieve to obtain an electrode active material.
[0162] <Physical properties of electrode active materials> The electrode active material obtained above was examined for the following properties.
[0163] (particle size distribution, median diameter) The particle size distribution was measured using a laser diffraction / scattering particle size distribution analyzer (Anton Paar PSA1090L particle size distribution analyzer) with water as the dispersion medium to obtain a particle size distribution curve. From the particle size distribution curve, the volume-based cumulative 50% diameter (median diameter d50) was measured.
[0164] (Elemental composition) The mass ratio (%) of the elemental amounts of carbon, hydrogen, nitrogen, and sulfur to the total amount of the electrode active material was calculated from the mass measured using a fully automatic elemental analyzer, Vario MICRO cube, manufactured by Elementar. The mass ratio (%) of the elemental amount of oxygen to the total amount of the electrode active material was calculated from the mass measured using an oxygen / nitrogen / hydrogen analyzer, EMGA-930, manufactured by Horiba, Ltd.
[0165] <Production of lithium-ion secondary battery> A lithium ion secondary battery was fabricated as follows.
[0166] (positive electrode) The electrode active material obtained above was used as the active material, acetylene black (HS-100, manufactured by Denka Co., Ltd.) as the conductive assistant, and acrylic resin (average molecular weight 2700-7500, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as the binder. These were weighed so that the ratio was active material: acetylene black: binder = 85: 10: 5 (mass%), and placed in a container. MilliQ water was used as a dispersant, and the mixture was stirred and mixed using a centrifugal mixer (ARE-250, manufactured by Thinky Co., Ltd.) to prepare a uniform slurry. The prepared slurry was applied to an aluminum foil of 17 μm using an applicator with a slit width of 100 μm, and the electrode compressed using a roll press was heated in a dryer at 120 ° C for 3 hours, dried, and punched out to φ11 mm to obtain an electrode (positive electrode). Thereafter, the mass of the electrode was measured, and the amount of active material in the electrode was calculated from the above ratio.
[0167] (Negative electrode) The negative electrode used was a metallic lithium foil (disk-shaped with a diameter of 14 mm and a thickness of 500 μm, manufactured by Honjo Metals Co., Ltd.) A stainless steel sheet was used as the negative electrode current collector.
[0168] (electrolyte) The electrolyte is a mixed solvent of ethylene carbonate and diethyl carbonate, and LiPF 6 The non-aqueous electrolyte used was a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1. 6 The concentration was 1.0 mol / L.
[0169] (Lithium-ion secondary battery) A coin battery was produced using the above positive and negative electrodes. In detail, in a dry room, a separator (Celgard2400 manufactured by Celgard, a polypropylene microporous membrane having a thickness of 25 μm) and a glass nonwoven fabric filter (440 μm thick, GA100 manufactured by ADVANTEC) were sandwiched between the positive and negative electrodes to produce an electrode body battery. This electrode body battery was housed in a battery case (a material for CR2032 type coin batteries, manufactured by Hosen Co., Ltd.) made of a stainless steel container. The above electrolyte was injected into the battery case. The amount was 0.28 mL in terms of the volume of the electrolyte. The battery case was sealed with a crimping machine to obtain the lithium ion secondary batteries of each of the Examples and Comparative Examples.
[0170] <Evaluation of lithium-ion secondary batteries> (discharge capacity, capacity maintenance rate) The coin-type lithium-ion secondary batteries produced in each of the Examples and Comparative Examples were charged and discharged at a current value equivalent to 50 mA for the first to tenth times per 1 g of positive electrode active material, and at a current value equivalent to 100 mA for the eleventh to twentieth times, under the condition of a test temperature of 30° C. The discharge end voltage was 1.0 V, and the charge end voltage was 3.0 V. The charging and discharging were repeated, and the battery discharge capacity (mAh) was observed for the first, second, tenth, and twentieth times. The measurements were performed using a battery performance evaluation device (BLS system, manufactured by Measuring Instrument Center Co., Ltd.).
[0171] Second discharge capacity DC 3 The initial capacity was determined as (mAh / g). The larger the initial capacity, the greater the charge / discharge capacity of the lithium-ion secondary battery, and the more favorable it is. 2 (mAh / g) and 20th discharge capacity DC 20 The capacity retention rate (%) was calculated from (mAh / g) using the following formula. It can be said that the higher the capacity retention rate, the more excellent the cycle characteristics of the lithium ion secondary battery. Capacity maintenance rate (%)=(DC 20 / DC 2 ) x 100
[0172] The results are shown in Table 1 below.
[0173] [Table 1]
[0174] Examples 1 to 4 showed higher initial discharge capacity than Comparative Examples 2 and 3. This is believed to be because the high sulfur content allows more binding with lithium ions. Note that, in Comparative Example 1, the initial discharge capacity is only lower than Examples 1 to 4, despite the high sulfur content. Moreover, Examples 1 to 4 showed higher capacity retention rates than Comparative Examples 1, 3, and 4. This is believed to be because the sulfur content was sufficiently high and the oxygen content was high, suppressing side reactions in the charge and discharge reaction.
[0175] <Embodiment> The following are preferred embodiments.
[0176] [1] An electrode active material comprising particles containing an organic sulfur compound, The oxygen content (mass%) in the electrode active material is A O and the sulfur content (mass%) is A S In the case where A O and A S and (3) satisfy the following formula, or at least one of the right sides of formulas (1) to (3) takes a more preferred value, wherein the preferred value for the right side of formula (1) is 10.0, the preferred value for the right side of formula (2) is 46.0, more preferably 47.0, even more preferably 48.0, and even more preferably 49.0, and the preferred value for the right side of formula (3) is 560. (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550 [2] The electrode active material according to the above [1], wherein the right side of the formula (1) is 11.0, preferably 12.0, more preferably 13.0, even more preferably 14.0, even more preferably 15.0, even more preferably 16.0, even more preferably 17.0, even more preferably 18.0. [3] The electrode active material according to [1] or [2] above, wherein the right side of formula (2) is 50.0, preferably 51.0, more preferably 52.0, even more preferably 53.0, even more preferably 54.0, even more preferably 55.0, even more preferably 56.0, even more preferably 57.0, even more preferably 58.0, even more preferably 59.0. [4] The electrode active material according to any one of the above [1] to [3], wherein the right side of the formula (3) is 570, preferably 600, more preferably 650, even more preferably 700, even more preferably 750, even more preferably 800, even more preferably 830, and even more preferably 840. [5] The electrode active material according to any one of [1] to [4] above, wherein the active material further comprises a metal compound containing at least one metal selected from the group consisting of iron, molybdenum, vanadium and titanium. [6] The electrode active material according to [5] above, wherein the metal compound is an iron compound. [7] An electrode comprising the electrode active material according to any one of the above [1] to [6]. [8] The electrode comprises a current collector; The current collector includes a metal foil, The coating density (mg / cm) of the electrode active material on the current collector 2 ) is D, then D and A O and A S or the right side of formula (4) is preferably 1500, more preferably 1700, even more preferably 1900, even more preferably 2100, even more preferably 2200, even more preferably 2300. (4) D×(A O ×A S )>1000 [9] The electrode comprises a current collector; The current collector includes a metal foil, The coating density (mg / cm) of the electrode active material on the current collector 2 ) is D and the thickness of the metal foil is T (μm), D, T and A O and A S The electrode according to [7] or [8] above, wherein the right side of formula (5) satisfies the following formula, or the right side of formula (5) is preferably 80, more preferably 90, even more preferably 110, even more preferably 120, and even more preferably 130. (5) D×(A O ×A S ) / T>60
[10] The electrode comprises a current collector; The current collector includes a metal foil, The coating density (mg / cm) of the electrode active material on the current collector 2 ) is D, where D is 2.50 mg / cm 2 More than 3.00 mg / cm 2 More preferably, 3.50 mg / cm 2 More preferably, 3.80 mg / cm 2 More preferably, 3.90 mg / cm 2 The electrode according to any one of the above [7] to [9], wherein the electrode is greater than 100%.
[11] The electrode according to any one of the above [7] to
[10] , wherein the electrode is a positive electrode.
[12] A lithium ion secondary battery comprising the electrode according to any one of the above [7] to
[11] .
[13] Further comprising an electrolyte, the volume of the electrolyte being V (mL); The coating density (mg / cm) of the electrode active material on the current collector 2 ) is D, then V, D and A O and A S and satisfies the following formula, or the right side of formula (6) is preferably 4500, more preferably 5000, even more preferably 5500, even more preferably 6000, even more preferably 7000, even more preferably 7500, and even more preferably 8000. The lithium ion secondary battery according to
[12] above. (6) D×(A O ×A S ) / V>4000
[14] A method for producing an electrode active material, comprising the steps of: (1) a mixing step of mixing a raw material containing cellulose and sulfur in a mass equal to or greater than the mass of the cellulose to obtain a calcined raw material; (2) a firing step of firing the firing raw material to obtain a fired product; and (3) A granulation step of pulverizing the fired product to obtain fired product particles. The method for producing an electrode active material includes the steps of:
[15] The method according to
[14] above, wherein the cellulose is not chemically modified. [Explanation of symbols]
[0177] 1 Muffle furnace 2 Heater 3 Lid 4. Inert Gas 5 Tray (upper) 6 Tray (lower) 7 Gas introduction pipe 8 Gas exhaust pipe 9. Sodium hydroxide solution 10 Trap tank
Claims
1. An electrode active material comprising particles containing an organic sulfur compound, The oxygen content (mass%) in the electrode active material is A O and the sulfur content (mass%) is A S In the case where A O and A S and satisfy the following formulas (1) to (3), The electrode active material further comprises a metal compound containing at least one metal selected from the group consisting of iron, molybdenum, vanadium, and titanium. (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550
2. An electrode active material comprising particles containing an organic sulfur compound, The oxygen content (mass%) in the electrode active material is A O and the sulfur content (mass%) is A S In the case where A O and A S and satisfy the following formulas (1) to (3), The electrode active material further comprises an iron compound. (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550
3. The electrode active material according to claim 1 or 2, wherein the right side of formula (1) is 11.
0.
4. The electrode active material according to claim 1 or 2, wherein the right side of formula (2) is 50.
0.
5. The electrode active material according to claim 1 or 2, wherein the right side of formula (3) is 570.
6. An electrode comprising the electrode active material according to claim 1 or 2.
7. An electrode active material comprising particles containing an organic sulfur compound, the oxygen content (mass%) in the electrode active material being A O and the sulfur content (mass%) is A S In the case where A O and A S and an electrode comprising an electrode active material satisfying the following formulas (1) to (3): The electrode includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm) of the electrode active material on the current collector is 2 ) is D, then D and A O and A S and an electrode satisfying the following formula (4). (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550 (4) D×(A O ×A S )>1000
8. An electrode active material comprising particles containing an organic sulfur compound, the oxygen content (mass%) in the electrode active material being A O and the sulfur content (mass%) is A S In the case where A O and A S and an electrode comprising an electrode active material satisfying the following formulas (1) to (3): The electrode includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm) of the electrode active material on the current collector is 2 ) is D and the thickness of the metal foil is T (μm), D, T and A O and A S and an electrode satisfying the following formula (5). (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550 (5) D×(A O ×A S ) / T>60
9. An electrode active material comprising particles containing an organic sulfur compound, the oxygen content (mass%) in the electrode active material being A O and the sulfur content (mass%) is A S In the case where A O and A S and an electrode comprising an electrode active material satisfying the following formulas (1) to (3): The electrode includes a current collector, the current collector includes a metal foil, and the coating density (mg / cm) of the electrode active material on the current collector is 2 ) is D, D is 2.50 mg / cm 2 An electrode that is super. (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550
10. The electrode of claim 6 , wherein the electrode is a positive electrode.
11. A lithium ion secondary battery comprising the electrode according to claim 6.
12. A lithium ion secondary battery comprising the electrode according to any one of claims 7 to 9.
13. An electrode active material comprising particles containing an organic sulfur compound, the oxygen content (mass%) in the electrode active material being A O and the sulfur content (mass%) is A S In the case where A O and A S and a lithium ion secondary battery comprising an electrode comprising an electrode active material satisfying the following formulas (1) to (3): The electrode further contains an electrolyte, the volume of the electrolyte being V (mL), and the coating density of the electrode active material on the current collector (mg / cm 2 ) is D, then V, D and A O and A S and a lithium ion secondary battery satisfying the following formula (6): (1) A O >9.0 (2) A S >45.0 (3) A O ×A S >550 (6) D×(A O ×A S ) / V>4000
14. A method for producing an electrode active material, comprising: (1) a mixing step of mixing a raw material containing cellulose and sulfur in a mass equal to or greater than the mass of the cellulose to obtain a calcined raw material; (2) a firing step of firing the firing raw material to obtain a fired product; and (3) A granulation step of pulverizing the fired product to obtain fired product particles. The method for producing an electrode active material includes the steps of:
15. The method according to claim 14, wherein the cellulose is chemically unmodified cellulose.
Citation Information
Patent Citations
Electrode slurry and method of manufacturing electrode using the same
JP2018055998A
Organic sulfur material, electrode and lithium-ion secondary battery, and production method
JP2021172814A
Sulfur-based positive electrode active material and lithium ion secondary battery
WO2015050086A1
Organic sulfur material and method for producing same
WO2016159212A1